DEVELOPMENT OF TEACHING MATERIALS BASED ON REALISTIC ALGEBRA AND MEASUREMENT MATERIALS - Mauluah, Luluk; Ekantini, Anita; Wijayanti, Inggit Dyaning (UIN Sunan Kalijaga Yogyakarta, 2024)
Students' understanding of mathematical concepts still needs to improve. This problem will spread to other subjects because mathematics is necessary for solving various problems. This research aims to determine the product development process for realistic teaching materials for mathematics, algebra material, and measurement and the feasibility of product development according to expert assessments and responses from potential users. This research is an RND with a 4-D development model which includes Define, Design, Develop, and Disseminate. The resulting product validator comprises three media, material, and discussion experts. Practitioner response testing was conducted on two 5th-grade teachers at Elementary School (SD) Muhammadiyah Sukonandi 2. The subjects for product testing were 5th-grade students at Elementary School (SD) Muhammadiyah Sukonandi 2. The instruments used in this research were questionnaires in the form of validation questionnaires, practitioner response questionnaires, and potential user responses. The assessment results from media experts scored 4.75 in the very good category, material experts scored 4.75 in the very good category, and language experts scored an average of 4.55 in the very good category. Practitioner response tests and user responses received very good responses.